2017
DOI: 10.1021/acsnano.7b05012
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Monolayer Two-Dimensional Lateral Quasi-Heterojunction Bipolar Transistors with Resonant Tunneling Phenomenon

Abstract: High-frequency operation with ultrathin, lightweight, and extremely flexible semiconducting electronics is highly desirable for the development of mobile devices, wearable electronic systems, and defense technologies. In this work, the experimental observation of quasi-heterojunction bipolar transistors utilizing a monolayer of the lateral WSe-MoS junctions as the conducting p-n channel is demonstrated. Both lateral n-p-n and p-n-p heterojunction bipolar transistors are fabricated to exhibit the output charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 43 publications
0
42
1
Order By: Relevance
“…Given the selective pn doping of 2D materials, a variety of fundamental devices that enable the digital technology can be developed, for example, pn diodes and amplifying bipolar transistors 28,29 . In optoelectronics, these devices based on pn junctions could manifest self-powered or fast and high gain photodetection beyond the usual photoconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the selective pn doping of 2D materials, a variety of fundamental devices that enable the digital technology can be developed, for example, pn diodes and amplifying bipolar transistors 28,29 . In optoelectronics, these devices based on pn junctions could manifest self-powered or fast and high gain photodetection beyond the usual photoconductors.…”
Section: Introductionmentioning
confidence: 99%
“…However, early attempts to construct the kind of devices relied prominently on locally buried gates 28 , lateral and vertical heterojunctions 3033 , the behavior of which are complicated to manipulate without fine-tuned pn doping. For example, the amplification gain in the resulting bipolar transistor is severely limited by the low carrier injection efficiency at the emitter–base junction, for example, based on MoS 2 /WSe 2 29 or MoS 2 /BP heterojunctions 34 . Moreover, these efforts fail to satisfy reconfigurable customization on demand with the predefined gate electrodes, epitaxial sequence in lateral junction, or stacking order in van der Waals heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other NPN HBT‐based MoS 2 /GaTe/n‐Si heterostructures were also fabricated using the same methods provided in Section 4 of the Supporting Information, whose characteristics are not as good as ours but also shows conventional NPN BJT characteristics. Our device performance and properties are compared with other reported HBT/HET devices based on 2D materials and listed in Table 1 36, 37, 38, 39, 40, 41. The theory of HETs is different than the theory of BJT/HETs, and there is a barrier between the emitter and the base layer in HETs.…”
mentioning
confidence: 99%
“…The current gain b of $6 is not too big but it is comparable to previously reported results. 32,34,35 There are two main reasons for the relatively low current gain. First, the gap size made by laser processing between the emitter and collector may be still large.…”
Section: Resultsmentioning
confidence: 99%
“…14 Multifunctional p-n diodes, 25,26 ultrasensitive photodetectors, 27,28 high-performance memories, 29,30 light-emitting diodes, 31 and bipolar junction transistors 32 have been fabricated from these materials, showing their potential application in future nanoelectronics. Although several studies on BJTs based on 2D van der Waals heterostructures can be found in the literature, [33][34][35][36][37][38] these structures have an intricate growth procedure 33,34 and tedious multistep transfer process, [35][36][37] making them difficult to fabricate. More importantly, one of the critical factors that inuences BJT performance is the difference in the major carrier concentration between the emitter and collector, which has never been explored until now.…”
Section: Introductionmentioning
confidence: 99%